Performance adaptation of gas turbines for power generation applications - Tsoutsanis, Elias (Cranfield University, 2010)
One of the greatest challenges that the world is facing is that of providing everyone access to safe and clean energy supplies. Since the liberalization of the electricity market in the UK during the 1990s many combined cycle gas turbine (CCGT) power plants have been developed as these plants are more energy efficient and friendlier to the environment. The core component in a combined cycle plant is the gas turbine. In this project the MEA’s Pulrose Power Station CCGT plant is under investigation. This plant cronsists of two aeroderivative LM2500+ gas turbines of General Electric for producing a total of 84MW power in a combined cycle configuration. Cont/d.